Composition Operators Mapping Logarithmic Bloch Functions into Hardy Space. (4th July 2018) - Kwon, E. G.
Abstract : Characterizing the hyperbolic Hardy classes, severalg -functions of hyperbolic type are introduced. Using this, necessary and sufficient conditions on the inducing self-maps are established for the boundedness of the composition operators from logarithmic Bloch spaces into Hardy spaces.